Simplified LRFD bridge design - 4 0 16; 1934- Kim, Jai B.,;Kim, Robert H.;Eberle, Jonathan R.; 5 (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2013)
Helping readers prepare for the civil and structural PE exam, this book presents numerous design examples that serve as a comprehensive, step-by-step guide to basic bridge design using the AASHTO LRFD Bridge Design Specifications, Fifth Edition. It offers a simplified explanation of load resistance factor design (LRFD) method-based bridge design principles and lists the AASHTO reference section numbers alongside formulas and where topics are introduced, to refer the reader to the primary source material. This is a valuable reference for civil engineering students as well as for practicing engineers--
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Design and construction;Examinations;Examinations;Examinations -- Iron and steel bridges;Load factor design;Structural engineering -- 20 -- Study guides.;Study guides.;Study guides; 20; 2